2018
DOI: 10.1007/s11120-018-0538-4
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal fungi (AMF) protects photosynthetic apparatus of wheat under drought stress

Abstract: Drought stress (DS) is amongst one of the abiotic factors affecting plant growth by limiting productivity of crops by inhibiting photosynthesis. Damage due to DS and its protection by Arbuscular Mycorrhizal fungi (AMF) was studied on photosynthetic apparatus of wheat (Triticum aestivum) plants in pot experiments. DS was maintained by limiting irrigation to the drought stressed (DS) and AMF + DS plants. Relative Water content (RWC) was measured for leaf as well as soil to ensure drought conditions. DS plants ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(109 citation statements)
references
References 48 publications
10
97
0
2
Order By: Relevance
“…Beneficial effects of AMF on chlorophyll fluorescence also have been reported by de Andrade et al (2015), who found that mycorrhizal rice plants had higher chlorophyll fluorescence under arsenate and arsenite pollution than non-mycorrhizal plants. Mathur et al (2019), studying the response of wheat to very severe drought, also noted a beneficial effects of AMF on chlorophyll fluorescence. However, Porce et al (2015) observed that mycorrhizal plants exhibited lower chlorophyll fluorescence than non-mycorrhizal plants, except at high salt levels where fluorescence values increased in mycorrhizal plants compared to a treatment with lower salt levels.…”
Section: Stomatal Conductance and Chlorophyll Fluorescencementioning
confidence: 97%
“…Beneficial effects of AMF on chlorophyll fluorescence also have been reported by de Andrade et al (2015), who found that mycorrhizal rice plants had higher chlorophyll fluorescence under arsenate and arsenite pollution than non-mycorrhizal plants. Mathur et al (2019), studying the response of wheat to very severe drought, also noted a beneficial effects of AMF on chlorophyll fluorescence. However, Porce et al (2015) observed that mycorrhizal plants exhibited lower chlorophyll fluorescence than non-mycorrhizal plants, except at high salt levels where fluorescence values increased in mycorrhizal plants compared to a treatment with lower salt levels.…”
Section: Stomatal Conductance and Chlorophyll Fluorescencementioning
confidence: 97%
“…Drought stress changes photosynthetic pigments and damages chloroplasts. Nonetheless, AM inoculation alleviates the damage of these parameters caused by the stress [77]. Rhizophagus irregularis-colonized castor bean plants subjected to water restriction increased contents of chlorophyll a (by 26%), b (30%), carotenoid (by 28.5%), and total chlorophyll (25.5%) in comparison to counterparts of non-AM plants [78].…”
Section: Increased Photosynthetic Efficiencymentioning
confidence: 98%
“…Numerous reports illustrate that AMF could increase photosynthetic activity or protect the photosynthetic apparatus under water stress conditions [77,78]. In fact, AM colonization considerably influences the stomatal behavior in the leaves of host plants, determining the water vapor efflux, CO 2 gas exchange, and thus photosynthetic activity [79].…”
Section: Increased Photosynthetic Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al (2018) [17] showed that maize plants appeared to have high dependency on AMF which improved physiological mechanisms by raising growth, chlorophyll content, gas exchange and rubisco activity under salinity stress. Mathur et al (2018) [18] showed that AFM plants increased relative water content both of plants leaf and soil indicating that AMF hyphae penetrated deep into soil and provided moisture to the plants. Thus this work was conducting to study the drought tolerance of maize plant at two different harvesting stages (30-and 90-days) and the combined action with mycorrhiza inoculation at these plant growth stages.…”
Section: Introductionmentioning
confidence: 99%